Ectomycorrhizal fungal diversity increases phosphorus uptake efficiency of European beech. Issue 4 (17th May 2018) - Köhler, Julia; Yang, Nan; Pena, Rodica; Raghavan, Venket; Polle, Andrea; Meier, Ina C.
Summary: Increases in summer droughts and nitrogen (N) deposition have raised concerns of widespread biodiversity loss and nutrient imbalances, but our understanding of the ecological role of ectomycorrhizal fungal (ECMF) diversity in mediating root functions remains a major knowledge gap. We used different global change scenarios to experimentally alter the composition of ECMF communities colonizing European beech saplings and examined the consequences for phosphorus (P) uptake (H3 33 PO4 feeding experiment) and use efficiencies of trees. Specifically, we simulated increases in temperature and N deposition and decreases in soil moisture and P availability in a factorial experiment. Here, we show that ECMF α diversity is a major factor contributing to root functioning under global change. P uptake efficiency of beech significantly increased with increasing ECMF species richness and diversity, as well as with decreasing P availability. As a consequence of decreases in ECMF diversity, P uptake efficiency decreased when soil moisture was limiting. By contrast, P use efficiencies were a direct (negative) function of P availability and not of ECMF diversity. We conclude that increasing summer droughts may reduce ECMF diversity and the complementarity of P uptake by ECMF species, which will add to negative growth effects expected from nutrient imbalances under global change.